Why do people drive when they can't see clearly?. (July 2018) - Fylan, F.; Hughes, A.; Wood, J.M.; Elliott, D.B.
Highlights: People do not feel obliged to wear their spectacles for driving. They believed they would know if their eyesight fails to meet minimum standards. Few recalled any conversations with or advice from their optometrist about driving. Better communication is important to prevent people driving uncorrected. Abstract: Purpose: Refractive blur is associated with decreased hazard perception and impairments in driving performance, but little is known about why people who have spectacles to correct their distance vision drive with uncorrected vision. Methods: We conducted six focus groups. Participants were 30 drivers (mean age 45) who reported having driven uncorrected at least twice in the past six months despite having spectacles to correct their distance vision. Focus groups were audio recorded, transcribed verbatim and analysed thematically. Results: We identified three themes. 1. Responsibility : participants did not feel obliged to drive with optimal vision and believed that others have a responsibility to ensure drivers maintain clear vision. 2. Safe Enough: participants felt safe to drive uncorrected, did not believe they need to wear spectacles to see sufficiently clearly and that they would know if their uncorrected eyesight fails to meet minimum standards. 3. Situations: participants discussed how they would drive uncorrected for short and familiar journeys, when they feel alert, in daylight and in good weather. Conclusions: Beliefs about the importance of driving with clear vision compete with the benefits of not wearing spectacles. Eyecare professionals should provide more direct advice to patients regarding the need to wear their visual correction for driving.